Enfermedades asociadas a la bronquiectasia en gatos: una revisión sistemática - Uribe Aguilar, Olga Marcela (2020)
The aim of this study was to systematically review the scientific evidence of diseases associated with bronchiectasis in cats, providing a better approach to diagnostic tests and related treatment. The OVID®, SciELO Citation Index® and Redalyc® search platforms were used. A research question was defined, and search terms were used to find relevant articles in the databases. Only original articles and case reports published in indexed journals and under peer review processes were considered, then filtered by title, abstract and full text. Subsequently, the reference lists of the definitive articles were searched for additional information (snowballing). Eight definitive articles were considered for the presentation of results and discussion (seven published in English and one in Spanish, between 1993 and 2019). From the information collected in the eight studies, it can be inferred that the response to treatment depends on the underlying disease, but that when a more chronic process occurs, it is difficult for the patient to respond to the management protocol, since bronchiectasis has no cure, and it is only possible, from the treatment, to delay its progression.